1998
DOI: 10.1002/(sici)1097-4644(19980501)69:2<127::aid-jcb4>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

DNA topoisomerase II can drive changes in higher order chromosome architecture without enzymatically modifying DNA

Abstract: Topoisomerase II has been suggested to play a major role in chromosome organization based on its DNA decatenating activity and its ability to mediate direct binding interactions between DNA and nuclear matrix. However, this latter point remains controversial. Here we address the question of whether the chromatin binding activity of Topoisomerase II is sufficient to modify chromosome form using whole mammalian chromosomes in vitro. Intact chromosomes were microsurgically removed from living cells and disassembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…Analysis of non-histone proteins in mitotic chromosomes found Fscaffold protein I_ (Lewis & Laemmli 1982), later identified as topo II , Gasser et al 1986. Electron-microscopic studies have indicated that topo II can bind a crossover of two DNAs (Zechiedrich & Osheroff 1990), and topo II has been observed to be able to recondense protease-decondensed chromosomes (Bojanowski et al 1998). Immunofluores-cence experiments have observed topo II localized in chromatid-axial patterns in mitotic chromosomes (Boy de la Tour & Laemmli 1988, Saitoh & Laemmli 1994, Maeshima & Laemmli 2003, Kireeva et al 2004, Maeshima et al 2005 (Figure 3).…”
Section: Topoisomerase IImentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of non-histone proteins in mitotic chromosomes found Fscaffold protein I_ (Lewis & Laemmli 1982), later identified as topo II , Gasser et al 1986. Electron-microscopic studies have indicated that topo II can bind a crossover of two DNAs (Zechiedrich & Osheroff 1990), and topo II has been observed to be able to recondense protease-decondensed chromosomes (Bojanowski et al 1998). Immunofluores-cence experiments have observed topo II localized in chromatid-axial patterns in mitotic chromosomes (Boy de la Tour & Laemmli 1988, Saitoh & Laemmli 1994, Maeshima & Laemmli 2003, Kireeva et al 2004, Maeshima et al 2005 (Figure 3).…”
Section: Topoisomerase IImentioning
confidence: 99%
“…The method is broadly similar to microneedle-based manipulation of meiotic metaphase chromosomes inside grasshopper spermatocytes (Nicklas 1963(Nicklas , 1983, as well as to classic studies of lampbrush chromosome mechanics (Callan 1954). Manipulation experiments without force measurement have been done by Maniotis et al (1997Maniotis et al ( , 2005 and Bojanowski et al (1998) who have developed methods for taking whole genomes out of cells using microneedles, and exposing them to changes in buffer conditions and enzymes.…”
Section: Chromosome-stretching Experimentsmentioning
confidence: 99%
“…It was shown that the endothelial cytoskeleton is at least indirectly (eg, via a signaling cascade including G-proteins and MAPKinases) connected to all shear stress receptors, 17,18 which were shown to signal to several endothelial compartments including the nucleus. 19,20 More than 40 genes have been reported to contain shear stress responsive elements (SSRE) within their promoter. The biomechanical stimulus finally leads to marked alterations in the expression of numerous genes.…”
Section: Physical Forcesmentioning
confidence: 99%
“…These mechanisms are still obscure (Bickmore & Chubb 2003). As a surprising possibility, a permanent physical link between chromosomes has been discussed (Nagele et al 1995) and, in some cases, experimentally evidenced (Maniotis et al 1997, Bojanowski et al 1998, Dozortsev et al 2000, Saifitdinova et al 2001). …”
Section: Introductionmentioning
confidence: 99%